Mitochondrial Calcium Uptake Capacity Modulates Neocortical Excitability. Issue 7 (July 2013) - Sanganahalli, Basavaraju G; Herman, Peter; Hyder, Fahmeed; Kannurpatti, Sridhar S
Local calcium (Ca 2 + ) changes regulate central nervous system metabolism and communication integrated by subcellular processes including mitochondrial Ca 2 + uptake. Mitochondria take up Ca 2 + through the calcium uniporter (mCU) aided by cytoplasmic microdomains of high Ca 2 + . Known only in vitro, the in vivo impact of mCU activity may reveal Ca 2 + -mediated roles of mitochondria in brain signaling and metabolism. From in vitro studies of mitochondrial Ca 2 + sequestration and cycling in various cell types of the central nervous system, we evaluated ranges of spontaneous and activity-induced Ca 2 + distributions in multiple subcellular compartments in vivo . We hypothesized that inhibiting (or enhancing) mCU activity would attenuate (or augment) cortical neuronal activity as well as activity-induced hemodynamic responses in an overall cytoplasmic and mitochondrial Ca 2 + -dependent manner. Spontaneous and sensory-evoked cortical activities were measured by extracellular electrophysiology complemented with dynamic mapping of blood oxygen level dependence and cerebral blood flow. Calcium uniporter activity was inhibited and enhanced pharmacologically, and its impact on the multimodal measures were analyzed in an integrated manner. Ru360, an mCU inhibitor, reduced all stimulus-evoked responses, whereas Kaempferol, an mCU enhancer, augmented all evoked responses. Collectively, the results confirm aforementioned hypotheses and support the Ca 2 + uptake-mediated integrative role of in vivo mitochondria on neocortical activity.